Differential circular RNA expression profiles in umbilical cord blood exosomes from preeclampsia patients - Minkai Cao; Juan Wen; Chaozhi Bu; Chunyan Li; Yu Lin; Hong Zhang; Yanfang Gu; Zhonghua Shi; Yan Zhang; Wei Long; Le Zhang (BMC, 2021)
Abstract Background Exosomal circular RNAs (circRNAs) are emerging as important regulators of physiological development and disease pathogenesis. However, the roles of exosomal circRNAs from umbilical cord blood in preeclampsia (PE) occurrence remains poorly understood. Methods We used microarray technology to establish the differential circRNA expression profiles in umbilical cord blood exosomes from PE patients compared with normal controls. Bioinformatics analysis was conducted to further predict the potential effects of the differentially expressed circRNAs and their interactions with miRNAs. Results According to the microarray data, we identified 143 significantly up-regulated circRNAs and 161 significantly down-regulated circRNAs in umbilical cord blood exosomes of PE patients compared with controls. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) biological pathway analyses showed that circRNA parental genes involved in the regulation of metabolic process, trophoblast growth and invasion were significantly enriched, which play important roles in PE development. Moreover, pathway network was constructed to reveal the key pathways in PE, such as PI3K-Akt signaling pathway. Further circRNA/miRNA interactions analysis demonstrated that most exosomal circRNAs had miRNA binding sites, and some miRNAs were associated with PE. Conclusions Our results highlight the importance of exosomal circRNAs in the pathogenesis of PE and lay a foundation for extensive studies on the role of exosomal circRNAs in PE development.